2021
DOI: 10.1002/ecs2.3420
|View full text |Cite
|
Sign up to set email alerts
|

An allometric niche model for species interactions in temperate freshwater ecosystems

Abstract: Trophic interactions are central in understanding ecosystem processes and the management of natural ecosystems but are frequently complex to estimate. To address this issue, body size has been shown to be a useful trait to reconstruct species interactions, particularly in aquatic ecosystems. An allometric niche model (aNM) considering body size as a niche trait is proposed to predict trophic interactions in temperate freshwater ecosystems. The aNM calibration was based on 26 ubiquitous freshwater species with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 73 publications
0
9
0
Order By: Relevance
“…The parameters c and r were estimated using a linear model and 5%–95% quantile regressions, respectively (Gravel et al, 2013). The aNM was calibrated using a set of 26 consumers covering wide taxonomic and body size diversities (i.e., from protists to piscivorous fish) for which diets and/or feeding ranges were already documented (see Vagnon et al, 2021 for more details). Due to vertebrate and invertebrate consumers differing in their feeding ranges, the aNM parameters ( c and r ) were estimated independently for these two taxonomic groups.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The parameters c and r were estimated using a linear model and 5%–95% quantile regressions, respectively (Gravel et al, 2013). The aNM was calibrated using a set of 26 consumers covering wide taxonomic and body size diversities (i.e., from protists to piscivorous fish) for which diets and/or feeding ranges were already documented (see Vagnon et al, 2021 for more details). Due to vertebrate and invertebrate consumers differing in their feeding ranges, the aNM parameters ( c and r ) were estimated independently for these two taxonomic groups.…”
Section: Methodsmentioning
confidence: 99%
“…Due to vertebrate and invertebrate consumers differing in their feeding ranges, the aNM parameters ( c and r ) were estimated independently for these two taxonomic groups. Vagnon et al (2021) validated the model using independent data and found that it predicts well empirical trophic links (accuracy = 81 ± 10%, equation 4 of Vagnon et al, 2021) (see also Supporting Information S4 for predator–prey mass ratio analysis and Supporting Information S5 for an analysis of the influence of fish body size on the niche attributes, trophic links, and food web metrics using either empirical body size measurements or body size estimates from the literature). Overall, the aNM provides integrative food webs including all realized trophic interactions although they are not necessarily realized simultaneously in nature.…”
Section: Methodsmentioning
confidence: 99%
“…We used the aNM (Vagnon et al, 2021) to infer trophic interactions between SC included in the typical peri-Alpine lake food web and to reconstruct the "non-invaded" (i.e., without S. glanis) and "invaded" food webs (i.e., with S. glanis). This model relies on the niche model principles (Williams and Martinez, 2000) stating that the niche position of consumer j is given by its average body size bs j and that its resources fall within a body size range bs_r j centered on bs_c j .…”
Section: Allometric Niche Model and Silurus Glanis Body Size Selectionmentioning
confidence: 99%
“…This model relies on the niche model principles (Williams and Martinez, 2000) stating that the niche position of consumer j is given by its average body size bs j and that its resources fall within a body size range bs_r j centered on bs_c j . The range bounds were estimated using quantile regressions (i.e., bs_r jmin = QR at 5% and bs_r jmax = QR at 95%) as suggested by Gravel et al (2013) and are specifically fitted whether consumers are vertebrate or invertebrate (Vagnon et al, 2021).…”
Section: Allometric Niche Model and Silurus Glanis Body Size Selectionmentioning
confidence: 99%
See 1 more Smart Citation